2021
DOI: 10.4081/jphia.2021.1455
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of reduced COVID-19 test time in controlling the spread of the disease: A simulation-based approach

Abstract: The novel coronavirus COVID-19 has known a large spread over the globe threatening human health. Recommendations from WHO and specialists insist on testing on a mass scale. However, health systems do not have enough resources. The current process requires the isolation of testees in the hospitals’ isolation rooms for several hours until the test results are revealed, limiting hospitals’ capacities to test large numbers of cases. The aim of this paper was to estimate the impact of reducing the COVID-19 test tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The simulation models were mainly used to assess the impact of COVID‐19 on an organization's workflow and emphasized its optimization (Allen, Bhanji, et al, 2020 ; Das, 2020 ; de Brito Jr et al, 2021 ; Kim et al, 2021 ; VanDeusen et al, 2021 ; Zeinalnezhad et al, 2020 ). Meanwhile, DES was also applied to process analysis and optimization of service facilities that had effects on COVID‐19 spread, including testing facility (Çaglayan et al, 2022 ; El Hage et al, 2021 ; Gowda et al, 2021 ; Saidani et al, 2021 ; Saidani & Kim, 2021 ), vaccination centres (Pilati et al, 2021 ) and COVID‐19‐related hospitals (Frichi et al, 2021 ; Melman et al, 2021 ). DES research was also used to investigate different interventions for minimizing transmission risk in lab facilities (Lim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The simulation models were mainly used to assess the impact of COVID‐19 on an organization's workflow and emphasized its optimization (Allen, Bhanji, et al, 2020 ; Das, 2020 ; de Brito Jr et al, 2021 ; Kim et al, 2021 ; VanDeusen et al, 2021 ; Zeinalnezhad et al, 2020 ). Meanwhile, DES was also applied to process analysis and optimization of service facilities that had effects on COVID‐19 spread, including testing facility (Çaglayan et al, 2022 ; El Hage et al, 2021 ; Gowda et al, 2021 ; Saidani et al, 2021 ; Saidani & Kim, 2021 ), vaccination centres (Pilati et al, 2021 ) and COVID‐19‐related hospitals (Frichi et al, 2021 ; Melman et al, 2021 ). DES research was also used to investigate different interventions for minimizing transmission risk in lab facilities (Lim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…As airborne transmission of SARS-CoV-2 is still being studied, the concentration of airborne contaminated particles has not been defined (ZHOU et al, 2021). However, it is known that there is enough risk to generate a probable infection, making confined environments a reasonable degree of risk (FRICHI et al, 2022). Thus, an enclosed environment with refrigeration is suitable place that favors the spread of viruses (CHAN et al, 2011).…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Studies have shown that the higher the humidity, the greater are the chances of these micro droplets colliding with other micro droplets of water, present in the air, thus becoming heavier and falling to the ground faster (MIGUEL e BABAK, 2020;CHAN, 2011;PRUSSIM, 2018;WAYMER, 2020). Obviously, this decreases the probability of spreading the disease through the air, which is one of the most important modes of dissemination (FRICHI et al, 2022).…”
Section: Introductionmentioning
confidence: 99%